Ethical Challenges in Genomics Research A Guide to Understanding Ethics in Context - Boddington, Paula (Springer Berlin Heidelberg : Imprint: Springer, 2012)
New developments in science and technology have resulted in shifting ethical challenges in many areas including in genomics research. This book enables those who are involved in genomics research, whether as researcher, participant or policy maker, to understand the ethical issues currently developing in this field and to participate actively in these important debates. A clear account is given of how science and technology are outstripping the capacity of previous ethical regulations to cope with current issues, together with practical illustrations of possible ways forward. Key ethical ideas are presented, drawing on the history of research regulation and on an account of the particular challenges arising in the field of genomics. The book uses a grounded, practical approach to explaining ethical concepts and issues which is geared to enhancing interdisciplinary dialogue. Its broad approach to ethical issues includes relevant considerations from social psychology and there is a particular emphasis on understanding the problems of ethical regulations and practice in the institutional and social context of research. A glossary and numerous text boxes explaining relevant terms and key ideas help to make the work an invaluable resource for both beginners and experts in the field.